Bortezomib, thalidomide, and dexamethasone followed by double autologous haematopoietic stem-cell transplantation for newly diagnosed multiple myeloma (GIMEMA-MMY-3006): long-term follow-up analysis of a randomised phase 3, open-label study. Issue 12 (December 2020) - Tacchetti, Paola; Pantani, Lucia; Patriarca, Francesca; Petrucci, Maria Teresa; Zamagni, Elena; Dozza, Luca; Galli, Monica; Di Raimondo, Francesco; Crippa, Claudia; Boccadoro, Mario; Barbato, Simona; Tosi, Patrizia; et al.
Summary: Background: The phase 3 GIMEMA-MMY-3006 trial, which compared bortezomib, thalidomide, and dexamethasone (VTD) combination therapy with thalidomide and dexamethasone (TD) as induction therapy before and consolidation therapy after double autologous haematopoietic stem-cell transplantation (HSCT) for newly diagnosed multiple myeloma, showed the superiority of the triplet regimen over the doublet in terms of increased complete response rate and improved progression-free survival. We report the results from the final analysis of the study. Methods: In this randomised, open-label, phase 3 study, patients aged 18–65 years with previously untreated symptomatic multiple myeloma and a Karnofsky Performance Status of 60% or higher were enrolled at 73 centres in Italy. Patients were randomised (1:1) by a web-based system to receive three 21-day cycles of thalidomide (100 mg daily orally for the first 14 days and 200 mg daily thereafter) plus dexamethasone (total 320 mg per cycle; 40 mg on days 1–2, 4–5, 8–9, and 11–12 in the VTD regimen, and 40 mg on days 1–4 and 9–12 in the TD regimen), either alone (TD group) or with bortezomib (1·3 mg/m 2 intravenously on days 1, 4, 8, and 11; VTD group). After double autologous HSCT, patients received two 35-day cycles of either the VTD or TD regimen, according to random assignment, as consolidation therapy. The primary outcome was the rate of complete response and near complete response after induction (already reported). In this updated analysis we assessed long-term progression-free survival and overall survival (secondary endpoints of the study) with an extended 10-year median follow-up, and analysed the variables influencing survival. Analysis was by intention to treat. The study is registered with ClinicalTrials.gov, NCT01134484 . Findings: Between May 10, 2006, and April 30, 2008, 480 patients were enrolled and randomly assigned to receive VTD (241 patients) or TD (239 patients). Six patients withdrew consent before start of treatment. 236 (99 [42%] women) in the VTD group and 238 (102 [43%] women) in the TD group were included in the intention-to-treat analysis. The data cutoff date for this analysis was May 31, 2018. Median follow-up for surviving patients was 124·1 months (IQR 117·2–131·7). The 10-year progression-free survival estimate for patients in the VTD group was 34% (95% CI 28–41) compared with 17% (13–23) for the TD group (hazard ratio [HR] 0·62 [95% CI 0·50–0·77]; p<0·0001). 60% (95% CI 54–67) of patients in the VTD group were alive at 10 years versus 46% (40–54) of patients in the TD group (HR 0·68 [95% CI 0·51–0·90]; p=0·0068). VTD was an independent predictor of improved progression-free survival (HR 0·60 [95% CI 0·48–0·76]; p<0·0001) and overall survival (HR 0·68 [0·50–0·91]; p=0·010). The incidence of second primary malignancies per 100 person-years was 0·87 (95% CI 0·49–1·44) in the VTD group compared with 1·41 (0·88–2·13) in the TD group. Interpretation: Incorporation of VTD into double autologous HSCT resulted in clinically meaningful improvements in long-term progression-free survival and overall survival, confirming that a regimen including bortezomib and an immunomodulatory drug is the gold standard treatment for patients with newly diagnosed myeloma who are fit for high-dose chemotherapy. Funding: Seràgnoli Institute of Haematology, University of Bologna, and BolognAIL.